Communication Skills Virtual Training - Orey, Maureen (Association for Talent Development, 2021)
Communication Skills Virtual Training offers the crucial tools you'll need to help your workshop participants master the skills that drive performance. Providing your participants with a deeper more nuanced understanding of communication will give them a solid foundation upon which to build strong skills and relationships in the workplace. Derived from the first book in the ATD Workshop series, this edition focuses on delivering virtual training and workshops with practical, road-tested strategies and tactics for use at all levels of your organization. New content geared to virtual training is included in presentation materials, agendas, handouts, assessments, and tools. Communication Skills Virtual Training presents two-day, one-day, and half-day communication training programs, along with relevant chapters on needs analysis, design, delivery, facilitation, and evaluation of the training event.